Female sexual dysfunction and Escitalopram antidepressant - Ali Mahran; Ahmed Ezzat; Ahmed Ahmed; Alaa Taha (Egyptian Journal of Medical Research, 2022)
Depression is major risk factor for sexual dysfunction (SD),and vice versa. Relative to men, women are at increased risk for depression and anxiety, as well as increased risk of SD. Depression may impair sexual well-being by reducing motivation for or reward from engaging in pleasurable activities, interfering with intimate relationship, or increasing the risk  of smoking or substance abuse. SD associated with depression and SSRIs affects all phase of sexual activity, including desire, arousal, and orgasm. Escitalopram, is an antidepressant of the selective serotonin reuptake inhibitor (SSRI) group . Escitalopram is  principally used to treat major depressive disorder or generalized anxiety disorder . Escitalopram, like other SSRIs, can  provoke various types of sexual dysfunction such as anorgasmia,  decreased libido, genital numbness, and sexual anhedonia , pleasureless orgasm. Conclusion: Although escitalopram is associated with FSD , yet , females with mild to moderate depression disorder should be treated with it otherwise they will suffer from SD.